Inhibition of secretion of a mutant lipoprotein across the cytoplasmic membrane by the wild-type lipoprotein of the Escherichia coli outer membrane. - Lee, N (1983)
A globomycin-resistant mutant of Escherichia coli was found to produce a precursor of the major outer membrane lipoprotein (prolipoprotein), in which the glycine residue at position 14 within the signal peptide was replaced by an aspartic acid residue. The same mutation has been reported by Lin et al. (Proc. Natl. Acad. Sci. U.S.A. 175:4891-4895, 1978). The structural gene of the mutant prolipoprotein was inserted into an inducible expression cloning vehicle. When the mutant prolipoprotein was produced in lipoprotein-minus host cells, 82% of the unprocessed protein was found in the membrane fraction, with the remaining 18% localized in the soluble fraction. However, when the production of the mutant prolipoprotein was induced in the wild-type lpp+ host cells, only 31% of the mutant prolipoprotein was found in the membrane fraction, leaving the remaining 69% in the soluble, cytoplasmic fraction. In addition, the assembly of the wild-type lipoprotein in these cells was not affected, whether the mutant prolipoprotein was produced or not. These results suggest that secretions of both mutant and wild-type prolipoproteins utilize the same component(s) responsible for the initial stages of secretion across the cytoplasmic membrane. However, it appears that the wild-type lipoprotein has a higher affinity for these components than does the mutant lipoprotein.